Equine pediatric medicine - Barr, Bonnie S.; Bernard, William V.; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This systematicyet concise guide to equine pediatric medicine covers etiology, pathophysiology, clinical presentation, differential diagnosis, diagnosis, and management.Beginning with a thorough explanation of the physical examination, the chapters then take the reader through the different disorders associated with each body system,including liver, cardiovascular, respiratory, opthalmologic, endocrine, and muscoskeletal diseases.A brand new chapter on nutrition has been added to this fully revised text. The book is superbly illustrated throughout with photographs, diagrams, radiographs and tables, whilea new sectionof in-depthcase studies brings the information to life. Equine practitionerswill value this as a ready reference, whileveterinary students and technicianscan use it asa complete guide to equine pediatric disease.
chapter 1 Physical Examination / William V. Bernard -- chapter 2 Shock, Resuscitation, Fluid and Electrolyte Therapy / Kevin T.T. Corley and Bonnie S. Barr -- chapter 3 Infectious Diseases / Bonnie S. Barr -- chapter 4 Immunologic and Hematologic Disorders / William V. Bernard -- chapter 5 Alimentary Tract Disorders / William V. Bernard -- chapter 6 Liver Disorders / William V. Bernard -- chapter 7 Cardiovascular Disorders / Johanna M. Reimer -- chapter 8 Respiratory Disorders / Bonnie S. Barr -- chapter 9 Urinary and Umbilical Disorders / Johanna M. Reimer -- chapter 10 Neurologic Disorders / William V. Bernard -- chapter 11 Muscle and Neuromuscular Junction Disorders / William V. Bernard -- chapter 12 Joint and Skeletal Disorders / Troy N. Trumble -- chapter 13 Ophthalmologic Disorders / Mary Lassaline -- chapter 14 Dermatologic Disorders / William V. Bernard -- chapter 15 Endocrine and Metabolic Disorders / William V. Bernard -- chapter 16 Neoplasia / Bonnie S. Barr -- chapter 17 Pharmacology -- chapter 18 Pediatric Nutrition / Bonnie S. Barr -- chapter 19 Case Studies / Laurie Metcalfe.
Keywords: Foals -- Diseases; Horses -- Physiology; Veterinary medicine; Veterinary pediatrics; TECHNOLOGY & ENGINEERING / Agriculture / Animal Husbandry